IMPROVING THE STUDENTS’ SPEAKING ABILITY OF ENGLISH COURSES BY USING OF DESCRIBING OBJECT TECHNIQUE - Armini1)*, Marzuki1) (Universitas Brawijaya, 2013)
The objective of this research was to know whether the Describing objecs Technique can improve students’ speaking ability effektively. The method of this research was quantitative approach. The instruments of the research were test items, observation sheet,. The test item consist of pre test and post test. The pretest was given to find out the ability of the students before they were given treatment, the posttest was given to find out the ability of the students after they were given treatment. Both of the pretest and post-test in the form of an oral test. The subject of the study was 15 students of Dena English Courses at Batu. The data of this research were collected by giving pre-test, observation, post-test. The collected data were noted and analyzed by using several statistics formulas. The results of data analysis showed that: Standard deviation of the result of average score was 14.4. The mean score of pretest was 36,2. The mean score of posttest was 49.7. The mean score from the pre –test and post-test was 13.5. And the result of t observation (tO) of the test was 3.6. At the degree of significance 5% = 2,14. The result is 2,14 < 3.6. Based on the data analysis above, the writer concluded that the increasing is significant at each language factor. Its meant that the describing objects technique has significance effect to improve the students’ speaking ability. And if the teacher frequent to use this technique, the students’ ability of speaking must be better Keywords: Speaking Ability, Describing Objects Technique, improve